2008
DOI: 10.1002/jcp.21657
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MAPK signaling on 1,25‐dihydroxyvitamin D‐mediated CYP24 gene expression in the enterocyte‐like cell line, Caco‐2

Abstract: We examined the role of the Extracellular signal Regulated Kinases (ERK) in 1,25 dihydroxyvitamin D (1,25(OH) 2 D 3 )-induced gene expression in the differentiated Caco-2 cells. 1,25(OH) 2 D 3 -regulated expression of the 25-hydroxyvitamin D, 24 hydroxylase (CYP24) gene (both natural gene and promoter construct) was strongly modulated by altering ERK activity (i.e. reduced by MEK inhibitors and dominant negative (dn) ERK1 and ERK2, activated by Epidermal Growth Factor) but ERK inhibition had no effect on 1,25(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
54
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 51 publications
7
54
0
Order By: Relevance
“…TRPV6 mRNA level is reduced by more than 90% in the duodenum of VDR knockout mice and the TRPV6 gene is strongly regulated by 1,25(OH) 2 D in the duodenum of mice [45,58] and in Caco-2 cells [59,60]. In addition, induction of TRPV6 mRNA precedes the increase in duodenal calcium absorption that occurs following a single 1,25 (OH) 2 D injection [45].…”
Section: Facilitated Diffusionmentioning
confidence: 96%
“…TRPV6 mRNA level is reduced by more than 90% in the duodenum of VDR knockout mice and the TRPV6 gene is strongly regulated by 1,25(OH) 2 D in the duodenum of mice [45,58] and in Caco-2 cells [59,60]. In addition, induction of TRPV6 mRNA precedes the increase in duodenal calcium absorption that occurs following a single 1,25 (OH) 2 D injection [45].…”
Section: Facilitated Diffusionmentioning
confidence: 96%
“…Involvement of specific MAPK-ERK signaling pathways in 1,25(OH) 2 D 3 -mediated activation of the CYP24A1 promoter may also be specific to the stage of cell differentiation. Cui et al reported that ERK1/2 signaling, but not ERK5, primarily regulates 1,25(OH) 2 D 3 -induced CYP24A1 mRNA expression in differentiated Caco-2 cells [115]. This contrasts with proliferating Caco-2 cells in which ERK5-mediated phosphorylation of Ets-1/EBS mainly potentiates 1,25(OH) 2 D 3 -mediated CYP24A1 gene transcription [115].…”
Section: Mapk Kinase Pathwaysmentioning
confidence: 96%
“…Cui et al reported that ERK1/2 signaling, but not ERK5, primarily regulates 1,25(OH) 2 D 3 -induced CYP24A1 mRNA expression in differentiated Caco-2 cells [115]. This contrasts with proliferating Caco-2 cells in which ERK5-mediated phosphorylation of Ets-1/EBS mainly potentiates 1,25(OH) 2 D 3 -mediated CYP24A1 gene transcription [115]. It will be interesting to establish the signaling pathways that utilize the interaction between the VDR and Ets-1 binding to modify vitamin D metabolism in disease states.…”
Section: Mapk Kinase Pathwaysmentioning
confidence: 98%
“…Cui et al, 16) reported that the accumulation of CYP24 mRNA induced by 1,25-(OH) 2 D 3 was significantly reduced in the presence of MEK inhibitor, but the impact of 1,25-(OH) 2 D 3 treatment on TRPV6, another VDR targeted gene, mRNA accumulation was not 15) or VDR (Silencer Select siRNA; Ambion, Grand Island, NY, USA). Knockdown efficiency was determined by Western blotting with the indicated antibodies.…”
mentioning
confidence: 98%
“…Hence Cui et al, claimed that vitamin D-dependent CYP24 but not TRPV6 gene expression requires ERK activity. 16) This suggests that the downstream effect of ERK on vitamin D is complex.…”
mentioning
confidence: 99%